Numerical Simulation of Performance Improvement of Underwater Lidar by Using a Spiral Phase Plate as Spatial Filter - YingQi Liao (IEEE, 2022)
In turbid water, target reflected lidar signal is easily buried in “clutter” due to scattering. We proposed an underwater laser ranging model applying an optical vortex in the receiver to separate the scattering clutter from the target reflected signal. A spiral phase plate (SPP) was placed in front of the detector to convert the target reflected Gaussian beam to an optical vortex. While the scattering clutters were not able to be converted due to the loss of spatial coherence. Therefore, the target reflected signal and scattering clutters were spatially separated by the SPP. An underwater laser detection simulation using Zemax software was carried out. The numerical simulation showed that when the SPP was placed in front of the receiver, the contrast of signal to clutter of the detection was improved by blocking the scattering clutters which had a Gaussian distribution at the center on the detection plane. The effects of beam divergence and orbital angular momentum (OAM) order to the lidar performance were also analyzed.